Country profile - Primary healthcare and family medicine in Namibia - Felicia Christians (AOSIS, 2020)
Namibia is one of the least densely populated countries in Southern Africa. Namibia's health services are twofold: private (serving 18% of the population with medical aid) and public (serving the remaining 82%). This, in part, is due to the country's high income inequality. Access to healthcare is comparably good with 76% of the population living within a 10km radius of a healthcare facility. Yet, Namibia faces many challenges related to the provision of patient-centred primary health care (PHC). The provision of competent generalist doctors and family physicians has the potential to address the current health care challenges and priorities. The inclusion of family physicians in PHC teams will further aid such efforts.